Cardiogenic Shock due to Kounis Syndrome following Cobra Bite. (4th August 2019) - Priyankara, W. D. D.; Manoj, E. M.; Gunapala, A.; Ranaweera, A. G. R. M. A.; Vithanage, K. S.; Sivasubramanium, M.; Snajeeva, E.
Abstract : Kounis syndrome is associated with mast cell activation resulting in acute coronary syndrome secondary to an allergic insult. Various drugs such as antibiotics, analgesics, and environmental exposures such as bee, wasp sting, and poison ivy are known to induce Kounis syndrome. A 68-year-old man admitted with a cobra bite on both hands to emergency care unit and sustained cardiorespiratory arrest. Electrocardiogram, taken 6 hours after the cardiac arrest, showed ST elevations in leads V2 to V5 suggestive of anterior ST elevation myocardial Infarction (STEMI). Serum Troponin was 10 ng/ml (control= <0.5). Serum IgE levels were significantly high (19155IU/ml, baseline 100). 2-Dimensional echocardiogram showed anterior and apical-septal hypokinesia with left ventricular ejection fraction of 30-35%. Coronary angiogram was normal. He remained hypotensive requiring inotropic and vasopressor support during ICU stay. This was a case of Kounis syndrome leading to cardiogenic shock secondary to Cobra (naja naja) bite. This is the only reported case of cobra bite causing Kounis syndrome and cardiogenic shock. Identification of the cause of myocardial infarction in snake envenomation is useful in the management as some of the drugs like adrenaline, morphine, and beta blockers may worsen the clinical syndrome if it is due to Kounis syndrome.